ANALYSIS OF THE LOGISTICS COST STRUCTURE OF MOCHI AHMAD YANI IN THE PREPARATION OF SUPPLY CHAIN STRATEGIES - Arista, Intan Nadyma; Rustilawati, Sindi; Lestari, Dewi; Rukasah, Wirasena (Syarif Hidayatullah State Islamic University Jakarta, 2024)
Mochi Sukabumi is a specialty food that has developed into one of the local culinary icons and has been recognized as an Intangible Cultural Heritage (WBTB) by the West Java Provincial Government in 2022. As a glutinous rice-based product with a relatively short shelf life, mochi Sukabumi requires effective and efficient supply chain management to maintain quality and meet consumer demand. This study aims to analyze the supply chain of Mochi Ahmad Yani, one of the pioneers of mochi in Sukabumi, with a focus on the management of raw materials, production, distribution and sales. Data were collected through in-depth interviews with business actors involved in the supply chain, namely suppliers, manufacturers, distributors, and retailers. This study used the Activity-Based Costing (ABC) method to analyze the logistics cost structure. The results show that procurement and material handling activities have the largest proportion of costs in the mochi supply chain, especially at the producer tier. The dominant cost structure in procurement is due to the need for quality raw materials to maintain product standards, while material handling costs are greater in distributors and retailers due to the handling of products directly related to end consumers. With an in-depth understanding of the logistics cost structure, Mochi Ahmad Yani is expected to formulate a more efficient supply chain strategy to improve competitiveness and customer satisfaction.